A catalogue of the types of Stratiomyidae (Diptera: Brachycera) in the collection of the Museu de Zoologia da Universidade de São Paulo, Brazil - Fachin, Diego Aguilar; Lamas, Carlos José Einicker (Zootaxa, 2015)
Following a recommendation of the International Code of Zoological Nomenclature, a catalogue of the type specimens of Stratiomyidae (Diptera: Brachycera) held in the collection of the Museu de Zoologia da Universidade de São Paulo, Brazil (MZUSP) is provided, with information on 30 type specimens (including 14 primary types) of 17 Neotropical species.